The Role of Human Resource Management in Service Sectors during Covid-19 Pandemic - Santi Santi; Athea Sarastiani; Lianna Wijaya; Sarfilianty Anggiani (University of Merdeka Malang, 2021)
In today’s business world, human resources are considered as an important resource for the organization’s success. To make better use of human resources, organizations must empower their employees This study aims to determine the impact of leading organization and leading people on trust and the organizational performance in the service sectors during Covid-19 pandemic. The research is quantitative, and the sampling technique is purposive sampling, with 103 respondents. Data collected were analyzed using Partial Least Squares path modeling to test the hypotheses. The study’s findings proved positive and significant linear relationship between leading people on trust and organizational performance. Managerial implication that the success leader in service sectors able to elevate trust among people, motivate the employees and to enhance organizational performance. As result, leadership training and elevate the trust amongst employees are the most essential strategies in service sectors during the Covid-19 pandemic.